Comparative Effects of Stevia rebaudiana and Aspartame on hepato-renal function of diabetic rats: Biochemical and Histological Approaches - Azza H. AbdElwahab, Asmaa F. Yousuf, Basma K. Ramadan, Hanan Elimam (Journal of Applied Pharmaceutical Science, 2017)
Diabetes mellitus is a chronic syndrome affecting many systems of the body and may be considered as a leading cause of death globally. To compare the efficacy of Stevia rebaudiana and Aspartame on hepato-renal functions, sixty adult male albino rats were divided into 6 groups; control, Stevia, Aspartame, diabetic, diabetic-treated with Stevia and diabetic-treated with Aspartame. Food consumption, body weight, blood glucose, serum aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (ALP), urea and creatinine levels were determined. Hepatic malondialdehyde (MDA), glutathione (GSH) and bcl-2 levels were assessed as well as histological examination for liver and kidney sections were performed. Treatment of diabetic rats with Stevia leaf extract or Aspartame significantly lowered food consumption and serum blood glucose. Serum blood glucose was significantly decreased by 38% with Stevia treatment and 50% with Aspartame. Stevia treatment of diabetic rats significantly lowered the serum level of ALT by 62%, AST by 57%, ALP by 41%, urea by 16% and creatinine by 65%. Hepatic MDA was reduced by 50% in diabetic group treated with Stevia and hepatic GSH and Bcl-2 levels were significantly elevated. In contrast, Aspartame did not change these parameters. Histopatholgically, diabetic rats treated with Stevia showed improvement of liver and renal tissues, while Aspartame treatment augmented alloxan induced tissue destruction. Aspartame was more effective hypoglycemic agent than Stevia in diabetic rats but Stevia showed protective effects on the liver and kidney functions. Stevia rebaudiana may be therapeutically beneficial as hepato-renal protective agent for those suffering from diabetes mellitus.
Keywords: Stevia rebaudiana,Aspartame,Alloxan,Hepato-renal functions,Diabetes mellitus.